Lower Plasma Elabela Levels in Hypertensive Patients With Heart Failure Predict the Occurrence of Major Adverse Cardiac Events: A Preliminary Study - Ma, Zheng; Zhao, Lei; Martin, Sara; Zhang, Yeping; Dong, Ying; Zhong, Jiu-Chang; Yang, Xin-Chun (Frontiers in Cardiovascular Medicine, 2021)
Background: Elabela, a novel cardiac developmental peptide, has been shown to improve heart dysfunction. However, the roles and correlation of Elabela in predicting adverse cardiac events in hypertensive patients with heart failure (HF) remain largely unclear. Objective: To measure plasma levels of Elabela in hypertensive patients with HF and evaluate its prognostic value. Methods: A single-site, cohort, prospective, observational study was investigated with all subjects, including control subjects and hypertensive patients with or without HF, whom were recruited in Beijing Chaoyang Hospital Affiliated to Capital Medical University form October 2018 to July 2019. The subjects among different groups were matched based on age and sex. The clinical characteristics were collected, and plasma Elabela levels were detected in all subjects. The hypertensive patients with HF were followed up for 180 days, and the major adverse cardiac events (MACE) were recorded. The Cox regression was used to explore the correlation between Elabela level and MACE in hypertensive patients with or without HF. The receiver operating characteristic curves were used to access the predictive power of plasma Elabela level. Results: A total of 308 subjects, including 40 control subjects, 134 hypertensive patients without HF, and 134 hypertensive patients with HF were enrolled in this study. Plasma levels of Elabela were lower in hypertensive patients compared with control subjects [4.9 (2.8, 6.7) vs. 11.8 (9.8, 14.0) ng/ml, P < 0.001]. Furthermore, HF patients with preserved ejection fraction had a higher plasma Elabela level than those with impaired left ventricular systolic function (heart failure with mid-range ejection fraction and heart failure with reduced ejection fraction). The hypertensive patients with HF and higher plasma Elabela levels had a better readmission-free and MACE-free survival than those with lower plasma Elabela levels in survival analysis. The Cox regression analysis revealed that plasma Elabela levels were negatively associated with MACE (HR 0.75, 95% CI 0.61–0.99, P = 0.048) in hypertensive patients with HF. Conclusion: Plasma Elabela levels were decreased in hypertensive patients with left ventricular systolic dysfunction. Thus, Elabela may be potentially used as a novel predictor for MACE in hypertensive patients with HF.